2016
DOI: 10.1093/mnras/stw577
|View full text |Cite
|
Sign up to set email alerts
|

Tracing black hole accretion with SED decomposition and IR lines: from local galaxies to the high-zUniverse

Abstract: We present new estimates of AGN accretion and star-formation luminosity in galaxies obtained for the local 12 µm sample of Seyfert galaxies (12MGS), by performing a detailed broad-band spectral energy distribution (SED) decomposition including the emission of stars, dust heated by star formation and a possible AGN dusty torus. Thanks to the availability of data from the X-rays to the sub-millimetre, we constrain and test the contribution of the stellar, AGN and star-formation components to the SEDs. The availa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 76 publications
(130 citation statements)
references
References 80 publications
7
123
0
Order By: Relevance
“…This result is in good agreement with diagnostics based on IR fine-structure lines: the strength of low-excitation lines, such as [Ne ii] 12.8 µm , compared to high-excitation transitions ([Ne v] 14.3 µm , [O iv] 25.9 µm ) suggests that star formation contributes about 67-70% to the gas ionisation, with a remaining 23-30% due to AGN activity (Section 4.1). Furthermore, similar values for the relative AGN/starburst contributions are derived from the decomposition of the mid-IR continuum, as shown by Gruppioni et al (2016). For these reasons we favour the extended core-halo configuration shown in Fig.…”
Section: A Compact Agn/starburst Nucleus?supporting
confidence: 84%
See 1 more Smart Citation
“…This result is in good agreement with diagnostics based on IR fine-structure lines: the strength of low-excitation lines, such as [Ne ii] 12.8 µm , compared to high-excitation transitions ([Ne v] 14.3 µm , [O iv] 25.9 µm ) suggests that star formation contributes about 67-70% to the gas ionisation, with a remaining 23-30% due to AGN activity (Section 4.1). Furthermore, similar values for the relative AGN/starburst contributions are derived from the decomposition of the mid-IR continuum, as shown by Gruppioni et al (2016). For these reasons we favour the extended core-halo configuration shown in Fig.…”
Section: A Compact Agn/starburst Nucleus?supporting
confidence: 84%
“…However, the W2 − W3 = 4.27 (4.6 to 11.6 µm) and W3 − W4 = 3.10 (11.6 to 22.1 µm) values place IC 3639 outside of the colour wedge defined by Mateos et al (2012) for luminous AGN, and rather close to the mid-IR colours of M82 or Arp 220. A more detailed analysis of the continuum emission for IC 3639 has been performed recently by Gruppioni et al (2016), using a broad-band UV to far-IR SED decomposition technique. The latter combines spectral templates of the dusty torus, the accretion disc, and various stellar populations (see Berta et al 2013 for further details).…”
Section: Ir Spectral Features and Coloursmentioning
confidence: 99%
“…10, for which we assumed the same correction for the quasar contamination to the FIR (50%) as for the measurements belonging to the samples from Netzer et al (2014Netzer et al ( , 2016 and from Fan et al (2016), which have similar properties. In contrast, we cannot make the same assumption for the objects by Gruppioni et al (2016): these are local sources at lower luminosity, therefore the quasar contribution to the FIR may be different compared to high-luminous sources. To be more accurate, we calculated the bisector of the two regression lines by first treating L QSO (dashed green line) as the independent variable and then considering the SF luminosity L SF as the independent variable (dot-dashed green line).…”
Section: Star Formation Rate Vs Black Hole Accretionmentioning
confidence: 95%
“…Black points represent the median value in a redshift bin. Gruppioni et al (2016) shown as brown circles and the quasar sample from the COSMOS survey (Bongiorno et al 2012), reported with density contours. The combination of these samples allows us to span a wide range of luminosity and redshift.…”
Section: Star Formation Rate Vs Black Hole Accretionmentioning
confidence: 99%
“…Therefore the equivalent widths of the PAH features enable us to roughly estimate the star-formation contribution to the total L IR of a galaxy (Moorwood 1986;Roche et al 1991;Genzel et al 1998;Armus et al 2007;Imanishi et al 2007Imanishi et al , 2008Imanishi et al , 2010Veilleux et al 2009;Nardini et al 2008Nardini et al , 2009Nardini et al , 2010Pope et al 2008;Menéndez-Delmestre et al 2009;Coppin et al 2010;Stierwalt et al 2013Stierwalt et al , 2014, and more reliably estimate it when they are normalized with other spectral indicators (such as H 2 or [NeII] 12.8 µm line fluxes) or the slope of the IR continuum (Tommasin et al 2010). This approach is complementary to the one that uses spectral energy distribution (SED) fitting (e.g., Gruppioni et al 2016;Delvecchio et al 2014). Although the PAH features are bright and readily identified, it is also known that their interband ratios can vary from galaxy to galaxy to some extent, mainly depending on their ionization states and/or size distributions which reflect the interstellar conditions (e.g., Allamandola et al 1989;Joblin et al 1994).…”
Section: Introductionmentioning
confidence: 99%